Julio César Avanza. A militant trajectory between Peronist and Catholic axiology: Peronist for Catholic or Catholic for Peronist? (Quinto Sol, 2023)
Values of the religious axiology of Catholicism and doctrines of Peronism permeated and mobilized the political action of vast sectors of women and men militants during the first presidencies of Juan Perón and the governorship of the province of Buenos Aires de Domingo Merchant. Tensions between Peronism and the Catholic Church, existing from times before the break of the 1954 relationship, imposed definitions in personalities identified with both axiologies about the priority of one or the other. By 1949 the Catholic Church was consolidating its aspiration to make Catholic education compulsory in the nation’s public schools and in the constitutions of several provinces. In the province of Buenos Aires, the Minister of Education (1949-1952) Julio César Avanza crowned the achievement of Catholicism. The object of analysis of this article is the recognition of the values that informed the discursive structure of Avanza from its beginnings in political militancy in 1944. The conceptual analytical question refers to how political and ideological values have interacted in the definition of acts of government in a militant trajectory.
Keywords: peronism; Catholicism; education; militancy